The effects of combination lime and organic amendments towards the rice growth grown on acid sulphate soil from Merbok, Kedah / Aizuddin Azim Mohammad Rosman Krishnan - Mohammad Rosman Krishnan, Aizuddin Azim (Faculty of Plantation and Agrotechnology, 2018)
An experiment was conducted in a greenhouse located at UiTM Jasin, Malacca to determine the best combination of organic amendments and lime towards rice growth grown on acid sulphate soil, in Merbok, Kedah. The growth and yield performance of rice (MR220) was measured based on the following parameters : ( i ) total number of tillers ; ( ii ) plant height, leaf length and chlorophyll content ; ( iii ) total yield. The pH and nutrient status of the soil was taken before and after the experiment. The experiment was set up as complete randomized design (CRD) with four replicates totaling 20 pots. The experiment included four treatments which were controlled (T0), cow manure (T1), goat manure (T2), chicken manure (T3) and empty fruit bunch compost (T4). MR 220 was used in the experiment because of the farmers in Merbok tend to use this variety in their field. The data of growth parameter and nutrient status of soil were collected in the third week after planting (3WAP), fifth week after planting (5WAP), seventh week after planting (7WAP), ninth week after planting (9WAP) and eleventh week after planting (11WAP). Organic amendments application increase soil pH and the nutrient content in soil. They also help in improving the growth performance of rice. Based on the result of this research, cow manure and empty fruit bunch compost with the mean of 5.617 and 5.607 showed significant increase in pH of soil. So, the best combination of organic amendment and lime was goat manure in order to increase, pH of soil, nutrient content, growth performance and yield of rice.